Effect of corrosion‐induced crack and corroded rebar shape on bond behavior. (28th March 2019) - Yang, Yizhou; Nakamura, Hikaru; Miura, Taito; Yamamoto, Yoshihito
Abstract : This paper aims to investigate the individual effect of corrosion‐induced crack, corroded rebar shape, and rust around rebar on the bond properties of reinforced concrete (RC) members. First, test specimens were corroded by accelerated electric corrosion method with varying corrosion degree ranging from 0 to 25%. Test specimens were divided into different groups. For the normal corrosion group, bond test was conducted directly after the corrosion test to investigate the combined effects including corrosion‐induced crack, corroded rebar shape, and rust on bond deterioration. In another group, after corroded rebar was taken out from test specimen, rust was removed before casted into new concrete to evaluate single effect of corroded rebar shape. Similarly, corroded rebar with rust was casted into new concrete to evaluate the effect of the formation of rust on bond degradation. Experimental results quantitatively illustrate the influential factors including corrosion degree, corrosion crack width and geometry of corroded rebar. As the important finding, corrosion crack in concrete is concluded to be a more dominant factor than the corroded rebar shape and rust accumulation in bond deterioration mechanism. Moreover, rust accumulation contributes to the improvement of bond deterioration induced by corroded rebar shape.